PHYTOCHEMICAL ANALYSIS AND IN VITRO INVESTIGATION OF ANTI-INFLAMMATORY AND XANTHINE OXIDASE INHIBITION POTENTIAL OF ROOT EXTRACTS OF BRYOPHYLLUM PINNATUM - A. Latif1; K. Ashiq; S. Ashiq; E. Ali; I. Anwer1and S. Qamar (Journal of Animal and Plant Sciences, 2020)
The aim of present study is to emphasize the phytochemical and biological studies of root extracts of Bryophyllum pinnatum, as little work was documented on the roots. Phytochemical analysis of powder and extracts were evaluated by the standard methods. UV/ Visible scanning, FTIR and atomic absorption spectroscopy were also performed for the purposes of standardization. In vitro anti-inflammatory investigation was done by protein denaturation method and xanthine oxidase inhibition assay was performed to confirm anti-gout effect. Phytochemical analysis results revealed the presence of primary metabolites (%w/w); carbohydrates (48.54+0.6) > proteins (21.06+0.6) > lipids (1.32+0.001). Secondary metabolites (mg/g) were also isolated; methanol extract has higher concentrations of flavonoids (95.81+0.026) and glycosaponins (39.9+0.103) while in water extract polysaccharide (139.4 + 0.026) and polyphenols (114.93+0.0234) were found to be in maximum quantities as compared to the other extracts. UV/Visible and FTIR scanning results have shown the presence of various significant functional groups. In vitro anti-inflammatory evaluation showed that aqueous extract (87.46%) was found to be the most active with IC50 (570.24ug/ml) as compared to the reference drug diclofenac sodium. In vitro xanthine oxidase inhibition activity was performed and methanol extract (88.24%) found to be the most effective. The findings confirm the plant nutritional value and rationale behind its use in traditional medicine for the treatment of inflammation and gout.
Keywords: Bryophyllum pinnatum; anti-inflammatory; gout; xanthine oxidase; phytochemical analysis